A transducing bacteriophage for Caulobacter crescentus uses the paracrystalline surface layer protein as a receptor. - Edwards, P (1991)
The bacteriophage phi Cr30, a transducing phage for Caulobacter crescentus strains, required the paracrystalline surface (S) layer for infectivity. Wild-type strains were phage resistant when rsaA, the gene for the 130K S-layer protein, was interrupted with an antibiotic resistance cassette. Strains that had lost the S layer by mutation were phage resistant, as were mutants that produce an S layer but which do not attach the structure to the cell surface. Phage sensitivity was restored to 130K-protein-deficient strains by introducing rsaA on a plasmid. Spontaneous phage-resistant strains produced expected phenotypes as follows (in order of decreasing frequency): S-layer cell attachment defects, no S layer, or an S layer that was wild type in appearance.